2008
DOI: 10.1016/j.vaccine.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A mimetics are potent adjuvants for an intranasal pneumonic plague vaccine

Abstract: An effective intranasal (i.n.) vaccine against pneumonic plague was developed. The formulation employed two synthetic lipid A mimetics as adjuvant combined with Yersinia pestis-derived V-and F1-protective antigens. The two nontoxic lipid A mimetics, classed as amino-alkyl glucosaminide 4-phosphates (AGPs) are potent ligands for the Toll-like receptor (TLR) 4. Using a murine (BALB/ c) pneumonic plague model, we showed a single i.n. application of the vaccine provided 63% protection within 21 days against a Y. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Prior work has shown that high antibody titers correlate with protection against live Y. pestis challenge [3][5], [7]. Consistent with a previous report [7], the soluble protein alone failed to provide protection against a lethal challenge, and mice vaccinated with S 50 generated low F1-V-specific antibody titers.…”
Section: Resultssupporting
confidence: 82%
“…Prior work has shown that high antibody titers correlate with protection against live Y. pestis challenge [3][5], [7]. Consistent with a previous report [7], the soluble protein alone failed to provide protection against a lethal challenge, and mice vaccinated with S 50 generated low F1-V-specific antibody titers.…”
Section: Resultssupporting
confidence: 82%
“…Presently, we are investigating whether dendritic cells participate in the persistence and dissemination of Y. pestis in vivo, since we know that D27-pLpxL potently activates dendritic cells and promotes their migration in vitro in a TLR4-dependent manner (35). Notably, Airhart et al recently described TLR4-activating lipid A mimetics that act as potent adjuvants for the F1/LcrV-based subunit plague vaccine (1). Future studies will need to determine whether increased TLR4 activation alone accounts for the robust immunity primed by D27-LpxL or whether transient persistence and/or dissemination also is a necessary criterion for the induction of protective cellular immunity by live attenuated Y. pestis vaccine strains.…”
Section: Discussionmentioning
confidence: 99%
“…Although the tumor cells were less responsive than DC to LPS, CXCL1 and CCL5 secretion by the tumor cells in response to LPS may be indicative of Myd88 dependent and TRIF dependent responses respectively since secretion of CXCL1 has been reported to be Myd88 dependent, and CCL5 secretion has been reported to be TRIF dependent [4, 33]. In particular, CXCL1 production by macrophages following treatment with LPS was dependent upon Myd88 [33], and CCL5 production by macrophages following exposure to Pseudomonas aeruginosa was dependent upon TRIF [4].…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of these receptors signaling cascades converge, promoting expression of inflammatory cytokines and type I interferons (IFN) the purpose of which are to assist in initiating a response against a pathogen [13]. Indeed, TLR signaling has been implicated in host protection by initiating antibacterial and antiviral responses [4, 5]. However, some detrimental effects have also been associated with TLR signaling such as with atherosclerosis and colitis [6, 7].…”
Section: Introductionmentioning
confidence: 99%